Pemeliharaan Preventif Pompa Vakum STG PLTGU Unit 1 Tambak Lorok Semarang - Win Alfalah (JURNAL POWERPLANT, 2018)
To increase the efficiency of condensation on the PLTGU (Gas and Steam Power Plant) a low pressure in condenser is needed, so steam moves faster toward the condenser because high pressure difference. To reduce pressure in the condenser, a vacuum pump is used. Vacuum pump engine maintenance in this study is in form of preventive maintenance (repairs carried out with the schedule scheduled by the component factory and/or by user experience), etc. This is because maintenance that is considered to be affordable both in terms of cost and field implementation in our country for power plants currently is preventive maintenance. What will be discussed here is preventive maintenance at the vacuum pump unit 1 of PT Indonesia Power PLTGU Tambak Lorok, Semarang. This discussion covers details of the vacuum pump preventive maintenance of each components, causal relationship of damage to causes, detailed analysis of the damage causes to vacuum pump components, etc.